Saraiki Proverbs Related to Runaway Women - Sultan, Sajid (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
The use of proverbs in the Saraiki language shows different male attitudes towards women especially ‘the runaway’. This research-based study is meant to highlight Saraiki proverbs related to runaway women and the negative attitudes they out forward declaring them careless and disobedient. There is a presumption that Saraiki-speaking women are hard working and less demanding. These proverbs present an ideal of Seraiki women as being very tolerant to the cruelties and hardships they face in the name of honor. Proverbs are mostly considered to reflect this taken-for-granted wisdom. This study will explore how these proverbs are deployed and what kinds of consequences they have both positive or negative.